2016
DOI: 10.1016/j.matdes.2016.08.062
|View full text |Cite
|
Sign up to set email alerts
|

3D printed polyurethane honeycombs for repeated tailored energy absorption

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractFused filament fabrication (FFF) 3D printing of thermoplastic polyurethanes (TPUs) offers a unique capability to manufacture tailorable, flexible cellular structures which can be designed and optimised for specific energy absorbing applications. This paper describes the first application of this methodology in the creation and experimental analysis of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(124 citation statements)
references
References 14 publications
3
105
0
3
Order By: Relevance
“…The softening behaviour during the first few compression cycles was also observed by Bates et al in their honeycomb 3D printed TPU foams after 5 cyclic compressions. 4 In a non-3D printed cylindrical TPU specimen (12 mm diameter and 3 mm height), the compressive stress-strain curve in the second cycle was far more compliant than that in the first cycle, and the stress-strain curves stabilized after the initial few compression cycles. 20 The foam's Mullins effect, and in particular its resilience, led to the conclusion that the 3D printed TPU foams fall into the category of rubber-like energy absorbers as opposed to most single-use cushion materials.…”
Section: Stress-strain Behaviourmentioning
confidence: 96%
See 1 more Smart Citation
“…The softening behaviour during the first few compression cycles was also observed by Bates et al in their honeycomb 3D printed TPU foams after 5 cyclic compressions. 4 In a non-3D printed cylindrical TPU specimen (12 mm diameter and 3 mm height), the compressive stress-strain curve in the second cycle was far more compliant than that in the first cycle, and the stress-strain curves stabilized after the initial few compression cycles. 20 The foam's Mullins effect, and in particular its resilience, led to the conclusion that the 3D printed TPU foams fall into the category of rubber-like energy absorbers as opposed to most single-use cushion materials.…”
Section: Stress-strain Behaviourmentioning
confidence: 96%
“…2 Bates et al used a basic hyperelastic honeycomb energy-absorbing structure and demonstrated the potential for 3D printed structures that demonstrated resiliency, good energy-absorbing efficiency, and quality of manufacture. 4 The study's conclusions were based on 5-cycle compression tests.…”
mentioning
confidence: 99%
“…As such, FDM 3D printing allows customization and fabrication of extremely complex geometries, maximizing material utilization and minimizing waste production compared to conventional manufacturing. In this context, FDM 3D printers have been used in a variety of fields such as biomedicine, nanotechnology, tissue engineering, and aerospace since they provide the possibility for the rapid printing of artificial bones, prosthetics, blood vessels, scaffolds for human tissues and organs, as well as complicated lightweight prototypes . Poly(lactic acid) (PLA) and acrylonitrile butadiene styrene (ABS) polymers are the two most common commercialized filaments used for FDM 3D printing prototype development .…”
Section: Introductionmentioning
confidence: 99%
“…Through an integration process, the absorbed energy can be obtained based on selected E s . 7 As discussed, energy absorption capability depends on relative density for the virgin honeycomb structure, suggesting 3D printed PCL polymeric honeycomb structure has better energy absorption capability than 3D printed PU polymeric honeycombs at RT. The absorbed energy upon the first compression (at RT) was 0.44 J cm 23 .…”
Section: Energy Absorptionmentioning
confidence: 86%
“…However, the shape of the cellular structures is limited to simple geometries by traditional manufacturing methods. Due to its rapid prototyping capability, complex structures such as construction of buildings, 13 tissue engineering, 14,15 and energy absorption structures, 7 could be printed through the attainable 3D printing process. Additive manufacturing technology can match this request, which could enable the fabrication of devices that are very geometrically complex and insistent on quality.…”
Section: Introductionmentioning
confidence: 99%